2014
DOI: 10.3109/19401736.2014.945544
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of the Clarias fuscus (Siluriformes, Clariidae)

Abstract: We present the complete mitochondrial genome of the Clarias fuscus in this study. The mitochondrial genome is 16,525 bp in length and consists of 13 protein-coding genes, two rRNA genes, 22 tRNA genes and a control region. The nucleotide compositions of the light strand are 31.17% of A, 27.54% of C, 25.34% of T, and 14.95% of G. With the exception of ND6 and eight tRNA genes, all other mitochondrial genes are encoded on the heavy strand. All the protein-coding genes begin with an ATG initiation codon except fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Gene arrangement and distribution of the three croakers were canonically identical and consistent with other vertebrates [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] but much different from the Mollusca [ 46 ]. However, the commonly discovered tRNA cluster Glu-Thr-Pro was not present in the three studied croakers or the other 9 studied teleosts [ 47 ], which covered Perciformes, Cypriniformes, and Siluriformes [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. The cluster tRNA-Glu - cyb-tRNA-Thr-Pro was available instead [ 48 ].…”
Section: Resultsmentioning
confidence: 52%
“…Gene arrangement and distribution of the three croakers were canonically identical and consistent with other vertebrates [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] but much different from the Mollusca [ 46 ]. However, the commonly discovered tRNA cluster Glu-Thr-Pro was not present in the three studied croakers or the other 9 studied teleosts [ 47 ], which covered Perciformes, Cypriniformes, and Siluriformes [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. The cluster tRNA-Glu - cyb-tRNA-Thr-Pro was available instead [ 48 ].…”
Section: Resultsmentioning
confidence: 52%
“…Various genetic markers (glutamic acid transfer RNA, cytochrome b, and cytochrome c oxidase subunit 1) were used to elucidate the diversity, evolutionary relationship, population structure, and cryptic diversity of Clarias species [ 23 , 24 , 25 ]. Later on, the complete mitogenomes and whole-genome sequences were analyzed to comprehend the in-depth phylogenetic relationship of Clarias species [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Further, with the flourishment of molecular tools in biodiversity research, the non-invasive environmental DNA (eDNA) was also examined by qPCR assay to reveal the genetic diversity of north African sharptooth catfish, C. gariepinus [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The overlapping of nucleotides between adjacent genes is a common characteristic found in teleost mitogenomes, which aids in compacting the mitogenomes [30,36]. The overlapping regions between ND4L/ND4 and ATP8/ATP6 were identi ed as common features found in Melanotaenia species [6,21,[26][27][28][29] and other teleosts [37][38][39][40]. In addition, in this study showed that greater diversity in both location and intergenic nucleotide lengths compared to the overlaps.…”
Section: Discussionmentioning
confidence: 59%